Isolated Solitary Intramedullary Spinal Cord Metastasis Presenting as the First Manifestation of Small-Cell Lung Cancer: Report of a Rare Case. (25th December 2012) - Duransoy, Yusuf Kurtuluş; Mete, Mesut; Selçuki, Mehmet; Işisağ, Aydın
Abstract : Background . Intramedullary spinal cord metastases presenting as the first manifestation of malignancies are extremely rare lesions. Case Description . The authors report a 74-year-old woman who presented with an isolated intramedullary spinal cord metastasis which presents as first manifestation of malignancy without central nervous system and/or other organ involvement. She went under surgery, and after histopathological evaluation, primary focus was determined in lung in positron emission tomography. She is still alive after 9 months since the first diagnosis of primary focus. Conclusion . In patients with solitary intramedullary lesion in the spinal magnetic resonance imaging, whole-body investigation might help for diagnosis of primary focus and approach to treatment.